Blocking lncRNA MALAT1/miR-199a/ZHX1 Axis Inhibits Glioblastoma Proliferation and Progression - Keman Liao; Yingying Lin; Weizhen Gao; Zhipeng Xiao; Rogelio Medina; Pauline Dmitriev; Jing Cui; Zhengping Zhuang; Xiaochun Zhao; Yongming Qiu; Xiaohua Zhang; Jianwei Ge; et al. (Elsevier, 2019)
Zinc fingers and homeoboxes 1 (ZHX1) is a transcription repressor that has been implicated in the tumorigenesis and progression of diverse tumors. The functional role and regulating mechanism of ZHX1 has not been elucidated in glioblastoma (GBM). Previous reports have suggested that a large number of non-coding RNAs play a vital role in glioma initiation and progression. This study aimed to investigate the functional role and co-regulatory mechanisms of the metastasis-associated lung adenocarcinoma transcript-1 (MALAT1)/ microRNA-199a (miR-199a)/ZHX1 axis in GBM. We analyzed the expression of the MALAT1/miR-199a/ZHX1 axis and its correlation with patients' overall survival using two different glioma gene-expression datasets. A series of in vitro and in vivo studies including dual luciferase reporter assay, fluorescence in situ hybridization (FISH), RNA immunoprecipitation, and pull-down experiments were completed to elucidate the biological significance of the MALAT1/miR-199a/ZHX1 axis in promoting glioma proliferation and progression. Elevated ZHX1 expression correlated with poor prognosis in GBM patients, and in vitro studies demonstrated that ZHX1 attenuated GBM cell apoptosis by downregulation of pro-apoptotic protein (Bax) and upregulation of anti-apoptotic protein (Bcl-2). Furthermore, knockdown of MALAT1 inhibited GBM proliferation and progression in vitro and reduced tumor volume and prolonged survival in an orthotopic GBM murine model. Finally, we demonstrated that MALAT1 promoted ZHX1 expression via acting as a competing endogenous RNA by sponging miR-199a. The MALAT1/miR-199a/ZHX1 axis promotes GBM cell proliferation and progression in vitro and in vivo, and its expression negatively correlates with GBM patient survival. Blocking the MALAT1/miR-199a/ZHX1 axis can serve as a novel therapeutic strategy for treating GBM. Keywords: MALAT1, ZHX1, glioblastoma, competing endogenous RNA, long non-coding RNA